Fatty acid composition of plasma phospholipids and risk of prostate cancer in a case-control analysis nested within the European Prospective Investigation into Cancer and Nutrition. - Crowe, F; Allen, N; Appleby, P; Overvad, K; Aardestrup, I; Johnsen, N; Tjønneland, A; Linseisen, J; Kaaks, R; Boeing, H; Kröger, J; Trichopoulou, A; et al. (2008)
BACKGROUND: Plausible biological mechanisms underlie possible associations between fatty acids in blood and risk of prostate cancer; epidemiologic evidence for an association, however, is inconsistent. OBJECTIVE: The objectives were to assess the association between plasma phospholipid fatty acids and risk of total prostate cancer by stage and grade. DESIGN: This was a nested case-control analysis of 962 men with a diagnosis of prostate cancer after a median follow-up time of 4.2 y and 1061 matched controls who were taking part in the European Prospective Investigation into Cancer and Nutrition. The fatty acid composition of plasma phospholipids was measured by gas chromatography, and the risk of prostate cancer was estimated by using conditional logistic regression with adjustment for lifestyle variables. RESULTS: We found a positive association between palmitic acid and risk of total, localized, and low-grade prostate cancer. The risk of prostate cancer for men in the highest quintile compared with the lowest quintile of palmitic acid was 1.47 (95% CI: 0.97, 2.23; P for trend = 0.032). We found an inverse association between stearic acid and the risk of total, localized, and low-grade prostate cancer; men in the highest quintile of stearic acid had a relative risk of 0.77 (95% CI: 0.56, 1.06; P for trend = 0.03). There were significant positive associations between myristic, alpha-linolenic, and eicosapentaenoic acids and risk of high-grade prostate cancer. CONCLUSION: The associations between palmitic, stearic, myristic, alpha-linolenic, and eicosapentaenoic acids and prostate cancer risk may reflect differences in intake or metabolism of these fatty acids between the precancer cases and controls and should be explored further.